Inner meaning fulfilment along differences in age, ethnicity, and educational background of the University Of Ibadan students (2005)
The increasing reports of maladaptive behaviour patterns exhibited by our various territary institutions in Nigeria had led to various responses from different relevant authorities. In the process of finding solution to these social menace, the study sought to find out inner meaning fulfillment (IMF)demographic variables such as age, ethnicity and educational background. There were eight hundred and eighty-five (885) participants with mean age of26.2 years and a standard deviation of 6.0 and age range from 15 - 60 years. The IMF scale (Logotest), which is a questionnaire format was used for the data collection in a survey/ ex-post facto design with randomly selected students within the university community. The findings were discussed in terms of the above three demographic variables differences in students' IMF. Implications of the findings were highlighted, discussed and suggestions made for the relevant authority in all the territory institutions in this country.